Role of satellite cells in skeletal muscle plasticity: Beyond muscle regeneration - Kotaro Tamura; Yasuro Furuichi; Yasuko Manabe; Nobuharu L. Fujii (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Satellite cells are resident muscle stem cells located between the basal lamina and the plasma membrane of myofibers. They play crucial roles in muscle growth during the postnatal stage and muscle regeneration following postnatal development. However, the roles of satellite cells in adult muscles - in muscle growth, function, and adaptation - are poorly understood. Recently, by studying genetically engineered mice with conditionally ablated satellite cells, it has been reported that satellite cells play important roles in muscle growth and maintenance of muscle spindles or neuromuscular junctions, and produce growth factors that affect other organs. Here, we review the recent studies using tamoxifen-inducible Pax7-DTA mice and describe the novel roles of satellite cells in the maintenance of skeletal muscle plasticity.